‘Nulla sed vivit in memoria’. Archaeological Prospecting of the Relics of the Synagogue in Mikołów in Upper Silesia - Radosław Zdaniewicz (Fasciculi Archaeologiae Historicae, 2023)
In Mikołów (Upper Silesia), a synagogue building was blown up and demolished in 1972 – a significant event that is preserved in the memory of the local population. In 2023, on the initiative of local authorities and cultural institutions, archaeological and architectural reconnaissance surveys were conducted to uncover, survey, and document any surviving relics of the synagogue. The research yielded new, previously unknown information regarding the building’s construction, including the discovery of the presumed floor of the synagogue’s vestibule. The preserved and uncovered remains of the foundations were secured after the research was completed and will undergo revitalisation and partial reconstruction in the future.